Medição de desempenho numa confecção de vestuário: integrando ergonomia situada ao processo de implementação e uso de indicadores de desempenho - Pizo, Carlos Antonio (2011)
This research aims to describe, in the organizational dynamics of a clothing manufacturing industry of medium size, more specifically in their sewing unit, the changes occurred during the implementation and use of performance indicators when aggregated in their development concepts and methods of Situated Ergonomics. The Performance Measurement Systems (PMSs) has always been part of the organizations and in recent decades has become more important due to the competitiveness and constant changes of the market as well as evolving toward more balanced structures to include all important factors that influencing the organizations competitiveness. The motivation of this study was the observation that PMSs identifies the priorities of performance in a top-down flow within the organizational structure, usually leaving or passing through the strategy. This process presents a strong bias technocentric, in which it aims to understand the structure and the organization's business processes and relegates to other instances much of real parts which are run by people in the everyday operations. Having the perception of this limitation, among other weaknesses in their development, deployment and use, many of these publishers of these models recommend that development is a participatory process, but does not define the way and depth to examine the reality of working at this level. Situated Ergonomics, in turn, pursued the objectives of well-being of the worker and process performance by analyzing the employee at work during the work activity and its effective contribution through verbalizations and confrontation of representations, so better understand their conditions and determinants. This Situated Ergonomics feature appeared to meet the limitation observed in the development of PMSs in a manner that sought to enter their concepts and methods during the development, deployment and use of performance indicators in the unit of sewing clothing manufacturing industry of medium size. The study was conducted through an action research which aimed to harmonize the cycles of intervention proposed by Haims and Carayon for the implementation of an ergonomics program, based on Situated Ergonomics, and the script development of PMS proposed by Andersen and Fagerhaug. The study indicated that by incorporating concepts and methods of ergonomics located in the development process and review of performance indicators this condition allowed the emergence of knowledge and collective needs, and develop a space for discussion and negotiation that enabled a better understanding of different views on the processes of transformation and its goals on the work carried out and performance indicators. In this context the incorporation proved to be mentioned as an important factor of change in the way the information is used by the SMD stakeholders. Despite the positive aspects of the negotiation space developed in these conditions, it was observed that this area is fragile in the face of contingencies that occur in a medium sized company.